Determination of fluoride level in drinking water from water samples in Navi Mumbai, Maharashtra - Sabita M Ram; Vaibhav Pravin Thakkar; Priyanka Machale (Wolters Kluwer Medknow Publications, 2017)
Introduction: The concentration of fluoride in drinking water influences the dental caries situation in the region. There are no studies reported determining the fluoride levels in drinking water supplies of Navi Mumbai. Aim: The aim of this study is to determine the fluoride level in drinking water samples from different areas of Navi Mumbai region. Materials and Methods: In an in vitro experimental study, water samples were collected from seven different locations of Navi Mumbai region. Water samples were collected from the Morbe dam, water purification plant at Bhokarpada in Raigad district, and five randomly selected residential areas of Navi Mumbai region. A total of 35 water subsamples were analyzed for fluoride content using fluoride analysis kit (HiMedia AQUACheck Fluoride Testing Kit). Results: The mean concentration of fluoride level in water samples from dam, water purification plant, as well as the five random residential areas was 0.5 mg/L (1 mg/L = 1 ppm). The fluoride level remained constant throughout from the source till the end consumer. Conclusion: There was no effect of water purification process at the plant on fluoride content of water samples. Similarly, the fluoride content was constant in the distributed purified water to residential areas. In this study, it was observed that the fluoride level in drinking water of Navi Mumbai was below the recommended levels by the World Health Organization as well as the Ministry of Health, Government of India.